Childhood ADHD and Involvement in Early Pregnancy: Mechanisms of Risk. Issue 14 (December 2020) - Meinzer, Michael C.; LeMoine, Kaitlyn A.; Howard, Andrea L.; Stehli, Annamarie; Arnold, L. Eugene; Hechtman, Lily; Hinshaw, Stephen P.; Molina, Brooke S. G.; Murray, Desiree W.; Sibley, Margaret H.; Swanson, James M.; Tamm, Leanne; et al.
Objective: ADHD is associated with risky sexual behavior and early pregnancy, but few studies have examined mechanisms of risk linking childhood ADHD to early pregnancy. The present study utilized data from the Multimodal Treatment Study of ADHD to examine potential mechanisms that may account for the association between childhood ADHD and becoming pregnant or causing a pregnancy by age 18.Method: Participants were 579 children with ADHD and 289 comparison peers followed over 16 years.Results: Relative to the comparison group, those with childhood ADHD were at more than two times increased risk of early pregnancy. Univariately, persistence of ADHD symptoms, delinquency/substance use, and academic performance/achievement during adolescence each mediated the association between childhood ADHD and early pregnancy. When considered together, only delinquency/substance use remained a significant mediator of this relationship.Conclusion: Findings point toward specific targets of intervention for youth with ADHD to prevent early pregnancy.